Factors Contributing to EFL Students’ Speaking Anxiety - Mulyono, Herri; Ferawati, Ferawati; Novita Sari, Ratih; Kusuma Ningsih, Sri (Register Journal, 2019)
This small-scale study aimed to factors that contribute to foreign language speaking anxiety among international tertiary students in Indonesia. The study drew on a qualitative method where seven International students studying at three universities in Indonesia were interviewed. The collected data then were transcribed and analyzed using a thematic analysis. The result revealed that the student participants experienced both facilitative and debilitative speaking anxiety when interacting with their peers during classroom learning. Language barriers, negative attitudes, intercultural communication apprehension were identified to provoke FLSA among the students. More importantly, these three factors also contributed to students’ feeling of speaking anxiety in their daily communication. Keywords: English as a Foreign Language (EFL), Foreign Language Speaking Anxiety (FLSA), Facilitative and Debilitative Speaking Anxiety